The DREB A-5 Transcription Factor ScDREB5 From Syntrichia caninervis Enhanced Salt Tolerance by Regulating Jasmonic Acid Biosynthesis in Transgenic Arabidopsis - Liu, Jinyuan; Yang, Ruirui; Liang, Yuqing; Wang, Yan; Li, Xiaoshuang (Frontiers in Plant Science, 2022)
Salinity is a major limiting factor in crop productivity. Dehydration-responsive element-binding protein (DREB) transcription factors have been widely identified in a variety of plants and play important roles in plant stress responses. Studies on DREBs have primarily focused on the A-1 and A-2 DREB groups, while few have focused on the A-5 group. In this study, we concentrated on ScDREB5, an A-5b type DREB gene from the desiccation-tolerant moss Syntrichia caninervis. ScDREB5 is a transcription factor localized to the nucleus that exhibits transactivation activity in yeast. Ectopic ScDREB5 expression in Arabidopsis increased seed germination and improved seedling tolerance under salt stress. ScDREB5-overexpression transgenic Arabidopsis lines showed lower malondialdehyde (MDA) and H2O2 contents, but higher peroxidase (POD), superoxide dismutase (SOD), and catalase (CAT) activities compared to wild plants. Moreover, the transcriptional levels of stress marker genes, including RD29B, COR47, LEA6, LEA7, ERD1, P5CS1, and salt overly sensitive (SOS) genes (SOS1, SOS2, and SOS3), were upregulated in the transgenic lines when subjected to salt treatment. Transcriptome and RT-qPCR analyses indicated that transgenic lines were accompanied by an increased expression of jasmonic acid (JA) biosynthesis genes, as well as a higher JA content under salt stress. Our results suggest that ScDREB5 could improve salt tolerance by enhancing the scavenging abilities of reactive oxygen species (ROS), increasing JA content by upregulating JA synthesis gene expression, regulating ion homeostasis by up-regulating stress-related genes, osmotic adjustment, and protein protection, making ScDREB5 a promising candidate gene for crop salt stress breeding.